Postcolonial trauma in selected Irish plays of the post 'troubles' period - Deena Mohamed Heggi; Amani Wagih; Reem Eldegwi (Cairo : Deena Mohamed Heggi, 2019)
This study explores the postcolonial Irish trauma, in a very crucial time of Irish history, adopting the psychoanalytic approach of the Indian political psychologist Ashis Nandy. In his book The Intimate Enemy: Loss and Recovery of Self under Colonialism (1983), Nandy emphasizes that "colonialism is first of all a matter of consciousness" (63). Thus, the study makes use of Ashis Nandy's theory to study the phenomenon of psychic trauma attempting to explore the origin and the reasons of the dilemma of the Irish self as portrayed in three postcolonial texts written in the post 'Troubles' period, the eighties and the nineties. In other words, the study links Nandy's concept of colonialism to the manifestations of the psychic trauma of the protagonists in selected Irish plays by three prolific Irish dramatists: Christina Reid's Tea in a China Cup (1983), Brian Friel's Dancing at Lughansa (1990), and Martin McDonagh's The Beauty Queen of Leenane (1996)
Thesis (M.A.) - Cairo University - Faculty of Arts - Department of English
Issued also as CD
Keywords: Irish plays; Plays; Postcolonial trauma